Protein sulphydryl depression during adjuvant arthritis. Issue 4 (August 1975) - Lorber, A; Leeb, J; Carroll, P; Baumgartner, W; Hill, V
Abstract : The changes in plasma protein sulphydryl level were measured during the course of adjuvant-induced arthritis in rats. Major depressions in the plasma sulphydryl level occurred at the onset of adjuvant disease, and the extent of the depression was related to the severity of the disease. Plasma sulphydryl levels remain unchanged when the systemic arthritis is suppressed by inclusion of a competing antigen in the adjuvant. Changes in sulphydryl content of the plasma were shown not to be due to weight loss or decrease in plasma protein level.